Rituals of Birth and Efforts to Preserving Cultural Identity in Cisaar Hamlet, Majalengka, Amidst the Tide of Modernization - Yunita, Shinta Alda; Kartika, Irma Dwi; Ratih, Dewi (Universitas Galuh, 2025)
This research aims to analyze the implementation process of the Nurunkeun Orok ceremony and examine its existence in the community of Dusun Cisaar in the modern era. Using a descriptive qualitative method with an ethnographic approach, the researcher was directly involved in the data collection process through observation, interviews, and literature review. The findings indicate that while Nurunkeun Orok involves a fairly long procession, the community of Dusun Cisaar has implemented simplifications without diminishing its essential inherent values in this modern era. This adaptation allows the ritual to remain relevant with the advancements of the times, while also serving as a crucial marker in the formation of both personal and collective identity.